2016
DOI: 10.1016/j.clnu.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malnutrition according to the new ESPEN definition in four diverse populations

Abstract: Using the ESPEN definition, 0%-14% malnutrition was found in the diverse populations. Further work is needed to fully address the validity of a two-step approach, including risk assessment as an initial step in screening and defining malnutrition. Furthermore, assessing the predictive validity of the ESPEN definition is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 8 publications
3
61
1
2
Order By: Relevance
“…In the present study, the prevalence of hospital malnutrition (according to ESPEN diagnosis criteria) was lower (20.5%) than that reported in the literature (20%–60%) but higher than that detected by the ESPEN criteria in a sample of 1014 elderly diabetic hospitalized patients (6.7%) previously evaluated for nutrition risk by the MNA . In the study conducted by Rojer et al in 4 different populations who were screened for nutrition risk by the SNAQ, the highest prevalence of malnutrition (14%) was found among acutely ill, middle‐aged patients . It is possible that the choice of the screening tool used to identify patients at risk of malnutrition contributes to differences in the prevalence of malnutrition among the studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In the present study, the prevalence of hospital malnutrition (according to ESPEN diagnosis criteria) was lower (20.5%) than that reported in the literature (20%–60%) but higher than that detected by the ESPEN criteria in a sample of 1014 elderly diabetic hospitalized patients (6.7%) previously evaluated for nutrition risk by the MNA . In the study conducted by Rojer et al in 4 different populations who were screened for nutrition risk by the SNAQ, the highest prevalence of malnutrition (14%) was found among acutely ill, middle‐aged patients . It is possible that the choice of the screening tool used to identify patients at risk of malnutrition contributes to differences in the prevalence of malnutrition among the studies.…”
Section: Discussioncontrasting
confidence: 69%
“…Furthermore, malnutrition lengthened the hospital stay, increased 2.7 times the odds of dying in the hospital, and decreased to one‐third the odds of being discharged home, suggesting that the new ESPEN definition is a reliable tool to predict clinical outcomes in older hospitalized patients with diabetes . In another study conducted in 4 populations, the prevalence of malnutrition according to ESPEN criteria was 14% in acutely ill middle‐aged patients, 6% in geriatric outpatients, 0.5% in healthy old individuals, and 0% in healthy young individuals …”
Section: Introductionmentioning
confidence: 99%
“…In the study by Rojer et al (40), which was the first to provide insight into the applicability of the new ESPEN consensus definition of malnutrition, the highest prevalence of malnutrition was in acute-ill patients (15%), being lower in geriatric outpatients and healthy old individuals; however, they did not study nursing home residents. With regard to the different diagnostic criteria of this consensus, only 6.25% had BMI < 18.5 kg/m 2 ; in fact, most men and women were overweight according to the BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In a large -scale survey, Kruizenga et al (17) reported that the departments with a high proportion of undernourished patients were geriatrics, oncology, gastroenterology, and internal medicine. Rojer et al (18) evaluated the nutritional status of four groups of subjects hospitalized middle -aged patients, elderly outpatients, healthy elderly people, and healthy young people based on a BMI of 18.5 or less, rate of weight loss, agecorrected BMI, and lean body mass and showed that the results were different for each group. We hope to develop a nutritional risk score that is specialized for patients with cancer who are undergoing outpatient chemotherapy by adding items such as type of cancer, department where the patient is treated, and symptoms, with the aim of providing continuous nutritional evaluation and management.…”
Section: Discussionmentioning
confidence: 99%